Evaluation of a Medium Chain Fatty Acid-Based Additive for Nursery Pigs - L. L. Thomas; H. E. Williams; J. C. Woodworth; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. M. DeRouchey; D. J. Mellick (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 350 pigs (DNA 400 × 200, initial BW = 13.8 lb) were used in a 34-d growth trial to evaluate the effects of increasing a medium chain fatty acid (MCFA)-based feed additive in nursery pig diets. Following arrival to the nursery research facility, pigs were randomized to pens (5 pigs per pen) and allowed a 4-d acclimation period. Thereafter, pens of pigs were blocked by body weight (BW) and randomized to 1 of 5 dietary treatments (14 pens per treatment). Treatments were constructed such that a dose response was created including 0, 0.5, 1.0, and 2.0% MCFA-based additive (CaptiSURE, Kemin Industries, Inc., Des Moines, IA) as well as a treatment including a 1.0% MCFA blend of C6, C8, and C10 (1:1:1 ratio; Sigma Aldrich, St. Louis, MO). Treatment diets were formulated and manufactured in two dietary phases (d 0 to 13 and 13 to 34). Overall (d 0 to 34), increasing CaptiSURE increased (linear,P≤ 0.014) average daily gain (ADG) and average daily feed intake (ADFI). Feed efficiency improved (quadratic,P= 0.002) with increasing CaptiSURE up to 1% of the diet with no benefit thereafter. As a result of these linear improvements in ADG, pigs fed 2.0% CaptiSURE were 4 lb heavier (P= 0.05) than pigs consuming diets without MCFA at d 34. There was no evidence for differences between the pigs fed 1.0% CaptiSURE and the 1.0% MCFA blend of C6, C8, and C10 in phase 1, phase 2, or in overall performance. In summary, the addition of this MCFA-based additive in nursery pig diets resulted in a linear improvement in ADG and ADFI. Based on these results, this MCFA feed additive appears to result in a similar improvement in growth performance as the C6, C8, and C10 MCFA blend when both are added at 1% of the diet. Additional research is warranted under commercial conditions to determine if similar advantages in growth performance are observed and if they provide an economic return.
Keywords: Growth; medium chain fatty acids; nursery pigs